Manual of structural design structural principles - suitable spans - inspiring works - Möller, Eberhard 1970- (DETAIL construction manuals, 2022)
Decisions regarding the supporting structure have an influence on the design of a building as well as an economic and ecological impact. The creation of great and innovative buildings requires close collaboration of architects, clients and structural engineers. Modern structural systems can benefit from an appropriate combination of various building materials. The "Atlas Tragwerke" (Support Structure Atlas) goes beyond material confines and showcases suitable construction principles for different building tasks. Classical masterpieces and outstanding current projects are used to demonstrate the potentials of structural systems for various building tasks and consider alternatives. Easy-to-compare structural principles offer a basis for a common level of communication in an interdisciplinary planning process.